Apprentissage de la lecture en français au cycle primaire. Analyse du manuel scolaire à la lumière de la psychologie cognitive - Atfa Memaï; Abla Rouag (Multilinguales)
This study focuses on the teaching and learning of reading in French as developed in the school textbook of the first year of learning French as a foreign language. It is the only textbook in Algeria for that level and for that discipline, since 2008. This paper compares the contents of this teaching support to recent research findings on learning to read in cognitive sciences and psychology. Relying on an analytical grid comprising ten (10) questions whose answers are distributed on a Likert -type scale. We conclude that the main principles and recommendations resulting from researches in psychology and cognitive sciences are not taken into account for the teaching of reading in this textbook.